Molecular diagnosis of Trichuris trichiura: Prevalence and associated risk factors in children under five living in a malaria-endemic area in Papua, Indonesia - Dhika Juliana Sukmana; Tri Nury Kridaningsih; Hartalina Mufidah; Enny Kenangalem; Faustina Helena Burdam; Tri Nugraha Susilawati; Jeanne Rini Poespoprodjo; E. Elsa Herdiana Murhandarwati (PLoS ONE, 2025)
Background Trichuris trichiura , a soil-transmitted helminth (STH), infection is highly prevalent in children and, if not treated, can cause adverse health consequences. Microscopy using the Kato-Katz method is the mainstay of STH diagnosis in most settings but has low sensitivity. This study aims to quantify prevalence and examine risk factors of trichuriasis among children in a malaria-endemic area. Methods The study recruited 181 children aged <5 years old from a household survey conducted in 16 villages in Timika, Papua, Indonesia, from April to July 2013. Clinical and laboratory data were collected, and stool samples were analysed later using quantitative PCR (qPCR). Results The prevalence of T. trichiura infections was 13.8% (25/181; 95%CI, 9.1–19.7) by Kato-Katz microscopy examination and 31.5% (57/181; 95%CI, 24.8–38.8) by qPCR analysis, increasing the prevalence by 17.7% (p = 0.0001). Children aged >3 years old had a 3 times increased risk of having trichuriasis compared to younger ones (aOR 3.29 [95%CI, 1.42–7.63], p = 0.006). Children with Hb ≤ 10 g/dL were 2 times more likely to have trichuriasis compared to those with Hb > 10 g/dL, (OR 2.46 [95%CI, 1.14–5.31], p = 0.020). Malaria prevalence was 9.9% (18/181; 95%CI, 6–15.3). Coinfections with malaria increased the risk of anaemia (OR 11.7 [95%CI, 2.0–67.0], p = 0.004. No apparent association was found between trichuriasis and undernutrition (wasting and stunting). Conclusions The prevalence of trichuriasis in under-five children is underestimated and together with malaria, the infections are associated with anaemia. Public health strategy should include STH prevention targeted to young children living in malaria-endemic areas.